Risk-adjusted trifecta outcomes in ultrasound-guided RFA of T1a renal masses: experience from a large tertiary cancer center - Derun Li; Jiyu Yang; Xiang Wang; Yi Liu; Gangzhi Shan; Zibo Zhang; Xu Han; Zhihua Li; Xuesong Li (International Brazilian Journal of Urology, 2025)
ABSTRACT Purpose: To evaluate the trifecta outcomes of ultrasound-guided radiofrequency ablation (RFA) of T1a renal masses and to identify factors influencing trifecta outcomes. Materials and Methods: We retrospectively reviewed data from patients who underwent ultrasound-guided RFA at Peking University First Hospital between March 2017 and May 2024. Baseline demographics, perioperative outcomes and follow-up results were collected. The trifecta outcomes were defined as the absence of severe complications, incomplete ablation and tumour recurrence. Multivariate logistic regression analysis was performed to identify risk factors for trifecta failure. Results: Among 270 patients (140 left-sided and 130 right-sided), the median tumour size was 1.97 (range 0.80-3.86) cm, and 32 (11.9%) patients had a history of ipsilateral partial nephrectomy. During the median follow-up of 35.6 (range 6.2-91.4) months, the rates of severe complications, tumour recurrence, and incomplete ablation were 1.1%, 7.4%, and 7.4%, respectively. The trifecta outcome was achieved in 227 (84.1%) patients. Multivariate analysis revealed that tumour size [odds ratio (OR): 2.144, p = 0.007] and history of ipsilateral partial nephrectomy (OR: 3.894, p = 0.002) independently predicted trifecta failure. Conclusion: Ultrasound-guided RFA is a safe and effective treatment for T1a renal masses. Tumour size and a history of ipsilateral partial nephrectomy were significantly associated with trifecta failure.